Bathless Inorganic Composite Nickel Plating: Dry‐Cell Stamping of Large Hygroscopic Phosphor Crystals. Issue 4 (7th January 2020) - Gerwitz, Caitlyn N.; David, Haley M.; Yan, Yifan; Shaw, Jason P.; Townsend, Troy K.
Abstract: In contrast to current composite‐metal electroplating, where objects are submerged into a liquid bath, a bathless aqueous inorganic electroplating method is investigated to increase composite loading and incorporation of large hygroscopic particles. This method can be applied as a stamping coating onto large or irregular conductive objects without the need for an electrolyte bath. Instead of stirring in solution, the composite particles are trapped in the electrolyte and forced to plate within the metal matrix. In this set‐up, a nickel salt mixture containing the composite is applied to the cathode and is separated from the anode with an ion‐permeable membrane. As a proof of concept, large noncharged fluorescent composite particles are electrochemically embedded via electrochemical reduction of nickel salts resulting in up to 80 ± 12% surface area coverage after controlling deposition parameters of current density and duration. Long persistent afterglow SrAl2 O4 :Eu 2+, Dy 3+ phosphor powder is chosen because of its large crystal size (87 ± 30 µm) and hygroscopic nature. The photoluminescent quantum yield is measured and compared to the composite coatings, which reaches up to 9.9 ± 0.8% after 18 h of coating. Film morphology, phosphor surface loading, and film thickness are characterized by optical microscopy. Abstract : A bathless aqueous inorganic composite electroplating method is demonstrated to produce fluorescent metal films containing high surface loadings of large hygroscopic particles.